On the curl and spring behaviour of CNC turned beryllium copper chips using computational image/video analysis. (1st August 2019) - Sooraj, V.S.; Nidish, Narayana; Nikhil, Anand; Priyanka, Chaudhary
Characteristic features of spring coiled chips generated during straight turning of Beryllium-Copper alloy have been studied using computational image and video analysis. Geometry and curl-behaviour of ductile chips leading to the formation of continuous helical coil structure is investigated theoretically and experimentally. Aiming the predictive generation of such chips for futuristic applications, theoretical relationships are derived to predict the curl radii and helix parameters in terms of cutting conditions and tool geometry. Cutting performances are also analysed at various conditions using the chip compression ratio, incorporating the inter-influence of major and minor cutting edges. A specially designed vibration test of metal chip followed by a computational video analysis is introduced in this work to assess their spring characteristics and stiffness. A simplified spring-beam analogy is applied for modelling the transverse vibration of chips using a clamped-free end condition, frequency of which is analysed from the videos and correlated to stiffness. Detailed experimental investigation followed by response surface analysis is reported to illustrate the geometrical features of chips at various cutting conditions.